2015
DOI: 10.3341/jkos.2015.56.12.1913
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in Intraocular Pressure Measured by Ocular Response Analyzer in Korean Patients with Normal Tension Glaucoma

Abstract: Purpose:To analyze the diurnal change in intraocular pressure (IOP) and corneal biomechanical properties measured using the Ocular Response Analyzer (ORA; Reichert Inc., Depew, NY, USA) in Korean patients with normal tension glaucoma (NTG) patients. ) and corneal hysteresis (CH), corneal resistance factor (CRF) and central corneal thickness (CCT) were measured in 21 eye of NTG patients (12 males, 9 female) at 3 hour intervals for 48 hours using ORA. We recorded the time of each parameter that showed the lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The relaxin softens the pelvic ligaments of the mother, so that the sacroiliac joints become relatively limber and the symphysis pubis becomes elastic. [23], [24] These changes make for easier passage of the fetus through the birth canal. Philips and Gore [23] suggested that this softening of ligaments in late pregnancy might extend to the ligament of the corneo-scleral envelope to produce reduced corneo-scleral rigidity and therefore cause a fall in IOP.…”
Section: Discussionmentioning
confidence: 99%
“…The relaxin softens the pelvic ligaments of the mother, so that the sacroiliac joints become relatively limber and the symphysis pubis becomes elastic. [23], [24] These changes make for easier passage of the fetus through the birth canal. Philips and Gore [23] suggested that this softening of ligaments in late pregnancy might extend to the ligament of the corneo-scleral envelope to produce reduced corneo-scleral rigidity and therefore cause a fall in IOP.…”
Section: Discussionmentioning
confidence: 99%